A Numerical Approach for Modelling of Polymer Curing in Fibre Reinforced Composites - Joshi, Sunil Chandrakant (2015)
This paper presents a procedure for using a general-purpose finite-element (FE) package for cure modeling. The package is used to carry out transient heat-transfer analysis and two user programs are developed to simulate resin-cure kinetics by using nodal control volumes based on the FE mesh. The theoretical background and numerical implementation of the procedure are described, and stability with respect to the FE mesh density and the length of the time step employed is investigated. Application of the procedure is demonstrated by modeling the cure of a thick prepreg laminate, a honeycomb sandwich panel and an I-beam. Predicted temperature profiles in the thick laminate are in excellent agreement with available experimental data.